Corticosteroid-free treatment of tocilizumab monotherapy for microscopic polyangiitis: a single-arm, single-center, clinical trial. Issue 6 (1st November 2016) - Sakai, Ryota; Kondo, Tsuneo; Kikuchi, Jun; Shibata, Akiko; Chino, Kentaro; Okuyama, Ayumi; Takei, Hirofumi; Amano, Koichi
Abstract: Objectives : To assess the efficacy of tocilizumab (TCZ) monotherapy for the remission induction of microscopic polyangiitis (MPA) in a prospective single-arm, single-center, cohort, pilot study. Methods : Eligible patients were aged between 20 and 80 years and were newly diagnosed with MPA according to Watts' classification algorithm. Seven patients received 8 mg/kg of intravenous TCZ fortnightly for the first 2 months (5 courses), and monthly for the next 10 months (10 courses). One year after TCZ monotherapy, the patients were followed-up without any treatment. The protocol did not permit the use corticosteroids or any other immunosuppressants. Complete remission (CR) was defined as the Birmingham Vasculitis Activity Score of 0 at two consecutive visits made at least a month apart. Results : CR was achieved in two of six patients (33.3%) at 6 months and three patients (50.0%) at 12 months. Two patients were withdrawn: one because of inefficacy at 6 weeks and the other because of flare at 6 months. One patient voluntarily withdrew after CR at 3 months. Four patients (66.7%) could be kept drug-free after 1 year of TCZ without relapse for 6–15 months at the last visit. Conclusion : TCZ monotherapy may be an alternative treatment strategy in some patients with MPA.